Pemanfaatan Pasar Tradisional sebagai Sumber Belajar pada Mata Pelajaran Ekonomi Kelas X - Ricardika, Dimas Caesar; Anisah, Aan (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2021)
This study aims to determine the use of the market as a learning resource and how to design LKS teaching materials. This study uses a qualitative research method with a case study approach. Data analysis techniques according to Miles and Huberman where the technique has four steps, namely data collection, data reduction, data display, and conclusion and verification of data. The results showed that economic activities in the Cilimus traditional market which can be used as a learning resource in Economics in the chapter material on Balance and Market Structure are: 1) Merchandise distribution activities, 2) merchandise storage, 3) presentation of merchandise Buying and selling transactions and the results of the validation of the design of environmentally based student worksheets show that this is feasible to be developed with some suggestions after validating material experts and media experts.